EMPLOYMENT OPPORTUNITIES FOR PERSONS WITH DISABILITIES IN INDONESIA: LEGAL STUDIES BASED ON THE SDGS PERSPECTIVE - Ayunda, Rahmi (Tadulako Law Review, 2021)
Persons with disabilities are humans who have certain physical or non-physical limitations that make them unable to do activities like humans in general. As part of Indonesian citizens, persons with disabilities have the same rights. These rights include life rights, education rights, health rights, household rights, political rights, development rights, and the right to get a job. Indonesia is responsible for the welfare of all its people including people with disabilities. This has been explicitly stated in the preamble to the 1945 Constitution of the Republic of Indonesia. However, the problem is that there are still people with disabilities who do not get their rights, especially the right to work. This research is important to do because it wants to examine the problem of employment opportunities for people with disabilities based on the perspective of the Sustainable Development Goals or SDGs. Generally, SDGs are intended to achieve social justice from generation to generation, including for people with disabilities. The 8th goal of the SDGs states explicitly that the state must be able to create decent jobs for all people without exception, including the provision of jobs for people with disabilities.